دراسة في معدل انتشار الأكزيمة البنيوية عند أطفال محافظة اللاذقية في سن المدرسة - الخير, عبد الله; دلـول, محمود; بدران, أيـهم (Latakia University Journal -Medical Sciences Series, 2019)
سبب الدراسة: تظهر التقارير الواردة من أقسام مختلفة من العالم بأن انتشار الأكزيمة البنيوية عند أطفال المدارس قد ارتفع بشكل كبير في الأربعين سنة الماضية. هدف الدراسة: التحقق من فائدة الاستبيان الأوروبي لتقييم انتشار الأكزيمة البنيوية عند أطفال محافظة اللاذقية في الريف والمدينة. الطرق: التقييم الذاتي بالاستبيان الأوروبي المعبأ من قبل الأهل لأطفال تتراوح أعمارهم بين12-5 سنة، من أربع مدارس ابتدائية في المدينة وثلاث مدارس ابتدائية في الريف. النتائج: أظهرت الإحصائيات انتشاراً بنسبة 9%، باستخدام الاستبيان الأوروبي. Background: Surveys from many parts of the world have shown that the prevalence of atopic dermatitis in schoolchildren has increased greatly in the past 40 years. Objective: Our objective was to investigate the utility of a European questionnaire to estimate the prevalence of atopic dermatitis in urban and rural Lattakia schoolchildren. Methods: The self-administered European questionnaire was completed by the parents of 5- to 12-year-old schoolchildren from four urban and three rural elementary schools in Lattakia. Results: Data showed a prevalence of 9% using the European questionnaire.